The Effect Of Applying The OSCE (Objective Structured Clinical Examination) Method On The Readiness for Practice In Clinical Practice In The S1 Study Program Of Stikes Kepanjen The Regency Of Malang - Zulfikar Muhammad (University of Muhammadiyah Malang, 2017)
Nursing students in the learning process will get in the classical learning and clinical practice. In switching between classical learning into clinical practice it needs for preparations and competency test before entering the practice field. One method of developing competency test in nursing is the OSCE (Objective Structured Clinical Examination). The purpose of this study is to determine the effect of the OSCE method on the readiness for practice in the S1 study program of STIKes Kepanjen. This research uses quantitative methods with the quasi experimental design and pretest posttest design with control group approach. The competency of the intervention group is assessed by using OSCE method and the control group by using conventional methods. This study compares the students’ readiness and student’s learning motivation on the pretest and on the posttest after respondents do the clinical practice. The data obtained were analyzed using t test with significance of ρ <0.05. This study has shown that the average value of readiness of respondents who are tested by using the OSCE method is 61.69 with the significance of 0.00, while respondents who were tested with the conventional method have the average value of 56.8 with a significance of 0.148. The mean posttest of the intervention and control group differed significantly with p value 0.000. The conclusionn in this study found that there is an increase in the readiness for practice in S1 study program of STIKes Kepanjen in which the one who are tested by using the OSCE method is higher than non OSCE method.